2014
DOI: 10.1002/bip.22524
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun tecophilic/gelatin nanofibers with potential for small diameter blood vessel tissue engineering

Abstract: Tissue engineering techniques particularly using electrospun scaffolds have been intensively used in recent years for the development of small diameter vascular grafts. However, the development of a completely successful scaffold that fulfills multiple requirements to guarantee complete vascular regeneration remains challenging. In this study, a hydrophilic and compliant polyurethane namely Tecophilic (TP) blended with gelatin (gel) at a weight ratio of 70:30 (TP(70)/gel(30)) was electrospun to fabricate a tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 63 publications
3
64
0
1
Order By: Relevance
“…Most research into TEVG has focused on the use of macromolecular synthetic materials, such as PGA [20, 21], polycaprolactone [27], polypropylene carbonate (PPC) [33], and electrospun tecophilic/gelatin nanofibers [34]. However, these yielded unsatisfactory long-term patency due to thrombotic failure in small-diameter vessels (<6 mm).…”
Section: Discussionmentioning
confidence: 99%
“…Most research into TEVG has focused on the use of macromolecular synthetic materials, such as PGA [20, 21], polycaprolactone [27], polypropylene carbonate (PPC) [33], and electrospun tecophilic/gelatin nanofibers [34]. However, these yielded unsatisfactory long-term patency due to thrombotic failure in small-diameter vessels (<6 mm).…”
Section: Discussionmentioning
confidence: 99%
“…Vasoactivity of contractile SMCs through vascular regeneration may enable the production of functional tissue-engineered blood vessels. We explained the potential of the sca olds to control the phenotypic modulation of SMCs in our previous studies and indicated the preservation of SMCs contractility on electrospun TP(70)/gel(30) sca olds [4,5]. While the proliferation of SMCs seeded on sca olds is generally essential to regenerate a vascular tissue, uncontrollable proliferation in the implanted graft can cause the thickening of the vessel wall and narrowing of the vessel lumen [7].…”
Section: Cell Growth and Morphologymentioning
confidence: 87%
“…The method of electrospinning has been described in our previous studies [4,5]. Brie y, respective polymer solutions prepared in HFP, either TP alone (8% w/v) or TP/gel solution, (8% w/v, with the blend ratio of 70:30 w/w, TP(70)/gel(30)) were individually loaded into a 3 mL plastic syringe tted with a 27 G blunted stainless steel needle.…”
Section: Fabrication Of Nano Brous Sca Oldsmentioning
confidence: 99%
See 2 more Smart Citations